Persepsi Guru PAI Tentang Integrasi Nilai-Nilai Karakter Islami dalam Proses Pembelajaran di SMA Bunda Kandung - Salmah Nurmar’atussolihah (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2026)
Rapid advances in digital technology have led to increasingly concerning changes in adolescent behavior, such as social media addiction and a decline in character awareness. These developments demand a significant shift in the role of Islamic Religious Education (IRE) teachers. This study aims to comprehensively examine how IRE teachers understand and implement character education in the face of an ever-evolving digital landscape. A qualitative descriptive method was used to collect data directly from IRE teachers through in-depth interviews, observations, and analysis of educational materials, thereby providing a snapshot of the current situation. PAI teachers view character education as a crucial response to student behavior that has been negatively influenced by digital technology, particularly regarding gaming addiction and age-inappropriate content. Specifically, Islamic Religious Education (PAI) teachers indicated that they utilize technology-based methods such as platforms including Islamic social media and digital learning environments while remaining aligned with religious principles. Additionally, the researchers found that these PAI teachers identified four key elements they emphasize in their teaching: strengthening faith as the foundation for character development, promoting ethical behavior through exemplary figures, enhancing religious understanding (fiqh and tafsir) as a guide, and studying Arabic as a tool for understanding